HUBUNGAN MEKANISME KOPING TERHADAP PERILAKU PENCEGAHAN SEKS BEBAS PADA REMAJA - Anisa Novianti; Herlina Herlina; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Coping mechanism is an individual's self-defense system, which is divided into two groups namely adaptive andmaladaptive. If the mechanism of individual coping maladaptif then tend to fall into the deviant behavior of one free sexand vice versa. The purpose of this study to determine the relationship of coping mechanisms against the preventionbehavior of free sex in adolescents. This research design use descriptive correlation with cross sectional approach. Thenumber of samples in this study as many as 73 people. Samples were taken using stratified random sampling techniquewith measuring instrument in the form of questionnaires that have been tested for validity and reliability. The result ofunivariate analysis showed that the average of respondent was in class XI that was 46 people (63,0%), female genderwas 40 people (54,8%), average age 16 was 37 people (50,7% %), the majority lived with 69 parents (94.5%), adaptivecoping mechanism was 39 people (53.4%) and who had active prevention behavior of 39 people (53.4%). The result ofbivariate analysis showed that there was correlation between coping mechanism toward the prevention behavior of freesex in adolescent (p value <α = 0,05) that is (0,02 ˂ 0,05) with value of Odd Ratio (OR) 3,2 value CI 95% its 1,231-8,438. The results of this study are expected to assist in the science of nursing and educational institutions to furtherimprove counseling services and conduct counseling about free sex so that adolescents can behave positively to preventfree sex.Keywords: adolescent, coping mechanism, free sex